THE EFFECT OF SIMULATION OF THE BASIC LIFE SUPPORT TRAINING ON NURSING STUDENTS' KNOWLEDGE - Ida Rahmawati; Dwi Putri Sulistiya Ningsih (Nurse and Health: Jurnal Keperawatan, 2020)
ABSTRACTBackground: Cardiac arrest is a health problem that is increasing to be the leading cause of death in the world. The main action to save cardiac arrest aims to maintain optimal myocardial and cerebral oxygenation so that death does not occur. Providing Basic Life Support (BLS) is an effort to save and restore this function. Knowledge about cardiac arrest among health students is still a neglected problem due to a lack of awareness in seeking basic knowledge.Objective: This study aimed to determine the effect of basic life support-based simulation training on knowledge of nursing students in the city of Bengkulu.Methods: This study used a pre-experimental design with a pre-test post-test approach. The population in this study were all 61 students of the fourth semester of STIKES Tri Mandiri Sakti Bengkulu nursing students. Samples were taken using total sampling technique. Data were collected using a knowledge questionnaire containing 10 question items which were adopted from the questionnaire Yunanto et al., (2017). Data were analyzed using paired sample t-test.Result: Based on the results of the study, it was found that there was a significant effect of BLS training based on manikin simulation on nursing student knowledge with a value of t test = -15.169, p = value = 0.000 <α = 0.05.Conclusion: Nursing students need to provide knowledge about BLS from the start so that they are more confident and able to apply it in case of cardiac arrest outside the hospital. Higher education institutions should provide health education about BLS from the beginning of the academic year, so that in the following semester students are better able to improve the quality of the skills they have formed.Keywords: Basic Life Support, Knowledge, Simulation.